Properties of Unburned Brick Produced by Entirely Waste-Stream Binder Activated by Desulfurization Gypsum - Lei Zhang; Lijie Guo; Yue Zhao; Mengyuan Li (Metals, 2022)
The massive accumulation of industrial solid wastes such as circulating fluidized bed fly ash (CFA), silicon-calcium slag (SCS), and desulfurization gypsum (FGD) occupy land resources and bring varying degrees of pollution to soil, water, and atmosphere. Unburned brick is a new construction material prepared from industrial waste residues such as fly ash and tailings without high-temperature calcination. It has excellent potential in consuming large quantities of industrial solid waste. In this paper, 70% of CFA and 30% of SCS are used as the primary raw materials, and the FGD is used as the activator to prepare unburned bricks by static pressure forming. The mechanical properties of the specimens at different curing ages were tested by compressive strength test. The hydration mechanism and microstructure of unburned brick were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS), thermogravimetric (TG), Fourier transform infrared spectroscopy (FTIR), and inductively coupled plasma-optical emission spectrometry (ICP-OES). The results show that the compressive strength of the specimen increases first and then decreases with the increase of FGD content, and the compressive strength reaches the maximum when the FGD content is 5%. The microscopic test results show that the presence of FGD promoted a higher degree of CFA and SCS dissolution, increasing ettringite formation, which is responsible for strength increase, but extreme doses of FGD resulted in strength degradation. Meanwhile, the higher SiO2/Al2O3 ratio confirms the simultaneous formation of hydrated calcium silicate (C-S-H) gel and hydrated calcium aluminosilicate (C-A-S-H) gel within the hydrated product, while a low SiO2/Al2O3 ratio confirms the simultaneous formation of ettringite.